Biomechanical evaluation of adjacent segment degeneration after one- or two-level anterior cervical discectomy and fusion versus cervical disc arthroplasty: A finite element analysis. (June 2020) - Hua, Wenbin; Zhi, Jinggang; Wang, Bingjin; Ke, Wencan; Sun, Wengang; Yang, Shuhua; Li, Li; Yang, Cao
Highlights: A finite element cervical model consisting of C2-C7 vertebrae was developed to compare the segmental range of motion (ROM) and intradiscal pressure after one or two-level anterior cervical discectomy and fusion (ACDF) and cervical disc arthroplasty (CDA). In both one- and two-level model of ACDF, the ROM of the fused segments were sacrificed, the ROM and intradiscal pressure at the adjacent segments were increased. However, in both one- and two-level model of CDA, the ROM of the surgery segments were preserved, avoiding the increase of the ROM and intradiscal pressure at the adjacent segments. Abnormal ROM and intradiscal pressure at the adjacent segments may contribute to the higher risk of adjacent segment degeneration after ACDF compared with CDA. Abstract: Background and objective: To compare the biomechanical changes of adjacent segment degeneration (ASD) after one- or two-level anterior cervical discectomy and fusion (ACDF) versus cervical disc arthroplasty (CDA). Methods: A three-dimensional finite element (FE) model of intact C2-C7 segments was constructed and validated. In the one-level surgery model, the cage with plate implant or Prestige LP cervical disc prosthesis were integrated at C5-C6 segment into the FE model; while in the two-level surgery model, the prostheses were integrated at both C4-C5 and C5-C6 segments into the FE model. A pure moment of 1.0 Nm combined with a follower load of 73.6 N were imposed on C2 to investigate the flexion-extension, lateral bending, and axial rotation of different segments in the FE model. The segmental range of motion (ROM) and intradiscal pressure of the surgery models were investigated and compared with the intact model. Results: In the one-level model of ACDF, the ROM at C5-C6 was decreased, the ROM and intradiscal pressure at C4-C5 and C6-C7 segments were increased. In the two-level model of ACDF, the ROM at C4-C5 and C5-C6 were decreased, the ROM and intradiscal pressure at C3-C4 and C6-C7 were increased. However, in both one- and two-level models of CDA, the ROM of surgery segments were preserved, avoiding the increase of the ROM and intradiscal pressure at the adjacent segments. Conclusions: Abnormal ROM and intradiscal pressure at the adjacent segments may contribute to the higher risk of ASD after ACDF compared with CDA.